Effects of heat generation and absorption on thermal radiative MHD flow of chemically reacting Casson nanofluids over a wedge - S. Venkateswarlu; B. Hari Babu; M. Veera Krishna (Case Studies in Thermal Engineering)
In engineering and technology, particularly in designing structures like ships, it can be difficult to allow fluids (like water) to flow smoothly around them. This is called a ''fluid combination problem.'' It is especially important when designing the hull (the bottom part) of ships. Engineers need to calculate the impact of water pressure on the hull and how the water's surface changes. These calculations help make sure that the hull is strong enough to handle different conditions, like waves or fast-moving water. In many engineering problems, geometries like wedges are used to model flow around objects. Studying flow over a wedge helps in understanding how fluids behave near sharp edges. This investigation represents the effect of thermal radiation, viscous dissipation on MHD of a chemically reacting flow of the Casson nanofluid across the moving wedge by the convective boundary conditions with internal heat generation/absorption. Silicon Dioxide (SiO₂) nanofluids are considered. The basic governing partial differential equations are converting into nonlinear ordinary differential equations with employing suitable similarity transformations. The resultant coupled non-linear ordinary differential equations are effectively solved numerically by the aid of MATLAB software. The variations of the relevant parameters on the velocity, temperature and concentration are investigated through graphs. The numeral quantities of skin friction coefficients, Nussult number and Sherwood numbers exhibited for the several sets of values of the physical parameters using graphical profiles. To vindicate the current analysis, the computational outputs are comparing by the previous available works which is accessible in the literature and they determined to be in the good concurrence. The main findings are the nanoparticle concentration profile decrease by increasing the values of the chemical reaction, Brownian motion and Schmidt parameter, and increases with enhance in the thermophoresis parameter.